Knowledge And Foot Care Behavior in Patients With Diabetes Melitus: Study of Corelation - Ida Nur Imamah; Guntur Harta Kusuma; Didik Iman Margatot (Universitas Duta Bangsa Surakarta, 2026)
Background: Hyperglycemic conditions can lead to microvascular (27.2%) and macrovascular (53.5%) complications. Hyperglycemia causes damage to nerve cells, resulting in neuropathy that leads to decreased protective sensation in the feet. This condition causes individuals with diabetes mellitus (DM) to be unaware of foot injuries. Proper foot care is an essential part of preventing diabetic foot ulcers and can be carried out by individuals with DM at low cost and with proven effectiveness. Foot care behavior refers to actions taken to maintain foot hygiene in diabetic patients and to prevent early injuries that could lead to infection risk. Knowledge serves as the foundation for behavior change and determines an individual's level of ability.Methods:This research is a quantitative study using a cross-sectional design. The population consists of all individuals with DM, with a sample size of 57 respondents in the Surakarta City prolanis group. The sampling technique used was accidental sampling. Data were analyzed using univariate and bivariate analysis.The research instrument used DFKS for knowledge and NAFF foot care behavior. Results:The majority of respondents had a low level of knowledge (64.9%) and poor foot care behavior (71.9%). Bivariate analysis using the chi-square test showed a p-value < 0.05 (0.018).Conclusion:There is a significant relationship between the level of knowledge and foot care behavior